Toxoplasma gondii and Rabies—The Parasite, the Virus, or Both? - Ragan Wilson; Shannon Caseltine; Edith Will; Jeremiah Saliki; Ruth C. Scimeca (Microorganisms)
Toxoplasma gondii is an intracellular protozoan parasite that infects a wide range of vertebrates, including humans. Although cats are the only definitive host, any warm-blooded animal can act as a paratenic host. Throughout the years, this apicomplexan parasite has been studied due to its wide prevalence, zoonotic potential, and host behavioral alterations. Known for its neurological alterations, the rabies virus is one of the most recognized types of zoonosis that, although preventable, still causes deaths in humans and animals worldwide. Due to the overlapping clinical signs of these two pathogens, the objective of this study was to evaluate the prevalence of T. gondii DNA in cerebellum tissue collected for rabies testing; cerebellum tissue from diverse animals is often submitted for this purpose. Between May 2022 and April 2024, we tested 903 cerebellum tissue samples from 22 animal species submitted for rabies testing to the Oklahoma Animal Diagnostic Disease Laboratory. Overall, T. gondii prevalence was 3.96%, with 1.8% found in cats (Felis catus), 1.7% in dogs (Canis familiaris), 0.3% in skunks (Mephitis mephitis), and 0.2% in infected cattle (Bos taurus). Analysis among T. gondii-positive hosts revealed a statistically significant difference in dogs when comparing neutered vs. intact males, with 7.94% (5/63) T. gondii-positive neutered males and 1.61% (3/186) T. gondii-positive intact males (p = 0.02). All the T. gondii-positive samples were negative for rabies. Anamnesis in some of the T. gondii-positive samples included ataxia, aggression, muscle rigidity, lethargy, and seizures, with the latter also described in dogs and aggression in the positive bovine sample. The clinical signs described in the T. gondii-infected hosts can be mistaken for rabies infection; therefore, it is important to consider T. gondii as a differential diagnosis in suspected rabies cases and test for this parasite when negative rabies results are obtained.